Pengaruh Kecerdasan Emosional, Kecerdasan Intelektual Dan Motivasi Terhadap Prestasi Kerja Pegawai - Andri Juliansyah; Ermila Octhari; Chamim Sumarno; Natasya Oktha Wijayanti; Novalina P; Tengku Ahmad Helmi (Journal of Business and Economics Research (JBE), 2022)
Employee performance is not the same result, this is because each employee has different abilities and willingness to carry out work, but if employees do not have achievements at work, this will have an impact on the progress of the organization. The problems are not optimal, not in accordance with standards, low competence and lack of fighting power in achieving work targets so that work performance is low. The purpose of this study was to determine and analyze emotional intelligence, intellectual intelligence and motivation to improve employee performance. This research is quantitative descriptive. Data collection techniques were carried out through interviews, questionnaires and documentation studies. The sample in this study were 45 employees. Variables were measured using a Likert scale. Hypothesis testing using multiple linear regression analysis through the F test and t test. The test results simultaneously show that the Effect of Emotional Intelligence, Intellectual Intelligence and Work Motivation on Employee Work Performance at the Regional Financial Management Agency, Revenue and Assets of the Tanjungbalai City Government with a value of Fcount > Ftable (7.752 > 2.812), and a significant value of 0.000". Intelligence intellectual has a positive and significant effect on work performance, income and regional assets with a value of tcount > ttable (2.854 > 0.679) and a significance value of 0.008 <0.05. Motivation has a positive effect on employee performance, income and regional assets with a value of tcount > ttable ( 1.431 > 0.679) and a significance value of 0.162 > 0.05. Intellectual intelligence is 118.1% and is the most dominant variable affecting employee performance.